Sustainability vs. Profitability: Dilemma or Synergy in Real Estate Companies - Shelfy Ananda Rahmatika; Imelda Zahrah Nabilah; Raluca Guse (Yayasan Az Zukhruf Cendikia, 2026)
Purpose – This study aims to analyze and identify the influence of environmental cost, carbon accounting, and corporate social responsibility on profitability. Design/methodology/approach – This study uses secondary data. The data were collected from companies operating in the property and real estate sector listed on the Indonesia Stock Exchange (IDX), with a total of 34 research samples for the period 2022-2024. The hypotheses were tested using a panel data regression model with the assistance of EViews. The research design employs a non-probability sampling method. Findings – The results of this study indicate that environmental cost has no effect no effect on firm value. Carbon accounting has a significant effect on profitability, and corporate social responsibility also has a significant effect on profitability. Research limitations/implications – The research was conducted solely on companies on the property and real estate subsector listed on the Indonesia Stock Exchange during the 2022-2024 period. The study used only financial reports and company sustainability reports. The adjusted R-squared value was 4.98%, indicating that environmental cost and carbon accounting variables could explain profitability. The R-squared value was 7.8%, indicating that the model’s ability to explain variations in profitability is still relatively low, suggesting that company profitability is influenced by many factors beyond environmental cost and carbon accounting. JEL : M41, M14, Q56, G30